Motivation and perception underlying farmers to improve the implementation of Good Agricultural Practices - Pepper (GAP-Pepper) - Yudi Sapta Pranoto; Sunarru Samsi Hariadi dan Alia Bihrajihat Raya (Journal of Global Innovations in Agricultural Sciences)
Motivation and Perception are psychological factors and essential capital that can influence farmers to improve the implementation of Good Agricultural Practices Pepper (GAP-Pepper). This study explores the underlying motivation and perception of farmers to be able to improve the implementation of pepper GAP, and its effects. this study uses a quantitative approach with a survey method, using a sample of pepper farmers in bangka belitung province, Indonesia, with a total of 270 victims, sampling using the multistage random sampling method—data collection using observation, interview, and questionnaire techniques with the Likert scale. The data was analyzed using descriptive statistics, and the path equation model used SPSS AMOS 22. The results showed that farmers' motivation was in the category of doubt to apply GAP Pepper, farmers' perception of GAP pepper was in a good category, and pepper farmers sometimes applied according to GAP's recommendations. Motivation hurts the implementation of the Pepper GAP, while the positive influence of farmers' perception has not been able to increase the implementation of the Pepper GAP. The positive influence on each GAP variable is land selection and cultivation (PpL) on crop cultivation management (PbT) and PbT on harvest and postharvest (PcP). To change the motivation and perception of farmers, access to resources, information, knowledge, and supporting technology is needed, as well as improving extension services to increase productivity and the existence of white pepper muntok (MWP). Keywords: Motivation, negative, perception, path analysis, sustainable, Muntok White Pepper (MWP), export products, Pepper Good Agricultural Practices (GAP-P).